LETRAMENTO LITERÁRIO: As obras maranhenses na formação do aluno-leitor no Ensino Médio - OLIVEIRA, Bruna Rafaelle Castro de (2024)
The present research aims to analyze to what extent the teaching of reading through Maranhão literary works, mediated by the Portuguese language teacher, has impacted reading practices and the formation of literary readers in the 3rd-year high school class at CE Nina Rodrigues School. The goal is to understand the resonance of reading local literary works in the development of readers. The study examines the theoretical and methodological concepts guiding literary literacy and teachers' reading practices in this class according to the DCTMA, identifying the strategies employed in the teaching- learning process when adopting a socio-interactionist approach. The research interprets data by combining bibliographic analysis, the review of normative documents, and the theoretical-methodological assumptions of collaborative action research. It employs pedagogical intervention research, focusing on the 3rd-year high school teacher and their respective class. The study involves interlocutors evaluated through observation, semi-structured interviews, discussion circles, and questionnaires as investigative tools. The findings reveal a lack of literary reading practices in the classroom that promote reader development and strategies facilitating the mediation between students and literary works. This highlights the need for a Guidelines Booklet to support pedagogical practices. The booklet, featuring four didactic sequences grounded in the interactive perspective of language as an example, aims to reframe literary reading practices in basic education.